(untitled) (Journal of Engineering, 2012)
The information required for construction quantities surveying is not only generated by various participants in different construction phases but also stored in different forms including graphics, text, tables, or various combinations of the three. To report a bill of quantities (BOQ), the project manager has to continuously excerpt information from various resources and record it on papers. Without adequate staff and time, this repetitive and tedious process is difficult for the project manager to handle properly and thus reduces the effectiveness and the accuracy of the quantities surveying process which creates problems during the design, tender, and construction supervision of construction projects for designers and contractors practicing because receipts are based upon actual quantities, such variations have an obvious impact on the contractor’s cash flow, once the actual quantities frequently vary from the estimated quantities listed in the BOQ. Hence, automation quantity surveying system has been developed by using GIS to extract the data required for the quantity of different components of any construction project from AutoCAD drawings (spatial data), to report a BOQ after querying, manipulation, and analyzing these data. The system has been implemented on the construction project of Al khawarizmy College at Baghdad University in Baghdad. The main results of using this system are automatic generation a bill of quantity (BOQ) directly from design drawing, with overcome to design changing, accurate, fast, and effective method for estimating the quantities, fewer errors in cost estimating, and better documentation for continuously reusing information in all construction phases. The accuracy of GIS quantities had been proved by comparing these quantities with the quantities of site surveying. Then determining the accuracy percentage (A%) of GIS quantities which equals (98.85%), and the regression line that equals 0.999. These values mean; there are big correlation between the estimated quantities by GIS and the quantities of site surveying.